WAYS TO INCREASE THE EFFICIENCY OF PRACTICAL EXERCISES - R.V. Qosimjonov (Galaxy International Interdisciplinary Research Journal, 2022)
This article focuses on the problems of improving the efficiency of practical exercisesin yardo physics b death. As a result of the subsequent development of this b death, new topics and the content of their corresponding practical workshopshave been developed. Practical workshops also outline ways to strengthen theoretical knowledge.